Opto-VLSI-based broadband true-time delay generation for phased array beamforming - Juswardy, Budi; Xiao, F.; Alameh, K. (2009)
Electronically controlled phased-array antennas can adaptively scan radiated beams in three-dimensional space without mechanically moving parts. While most of the research on phased-array antennas has been focusing on broadband beam steering less attention has been devoted to null steering. Broadband null steering requires a beamformer that can generate variable and frequency independent true time-delays (TTD). In this paper we propose and demonstrate the concept of an Opto-VLSI-based tunable true-time delay generation unit for adaptive null steering in phased array antennas, where arbitrary single or multiple true-time delays can simultaneously be synthesized. Simulated azimuth gain patterns for a 4- element antenna arrays is presented, and experimental results are shown, which demonstrate the principle of the proposed true-time delay unit. © 2009 Copyright SPIE - The International Society for Optical Engineering.